Minority Small-Firm Credit Applicants: Does Persistence Pay? - Grace Kim (The Journal of Entrepreneurial Finance (JEF), 2011)
When credit application experiences are examined, minority-owned small firms are not the discouraged borrowers that credit outcome studies generally suggest. This paper examines repeated application for credit by small firms. Univariate statistical analysis reveals that persistence is necessary but insufficient for minority firms to be successful credit applicants. At the same time, minority-owned firms overall were more likely than white-owned firms to make repeated attempts to obtain credit, though successful minority applicants actually required fewer applications than their white cohorts. Multivariate regression also finds that different firm, lender, banking relationship, and loan characteristics affect the continued search for credit by minority- and white-owned small firms.
Keywords: G20; M13; M20; 650; minority; small firms; credit search; discouraged borrower; persistence